OP0202 EFFECT OF RSLV-132 ON FATIGUE IN PATIENTS WITH PRIMARY SJÖGREN'S SYNDROME – RESULTS OF A PHASE II RANDOMISED, DOUBLE-BLIND, PLACEBO-CONTROLLED, PROOF OF CONCEPT STUDY. (June 2019) - Fisher, Benjamin; Barone, Francesca; Jobling, Kerry; Gallagher, Peter; Macrae, Victoria; Filby, Andrew; Hulmes, Gillian; Milne, Paul; Traianos, Emmanuella; Iannizzotto, Valentina; Dumusc, Alexandre; Bowman, Simon J.; et al.
Abstract : Background: Fatigue is the key symptom that leads to poor health related quality of life and loss of work productivity in patients with primary Sjogren's syndrome (pSS). RSLV-132 is a first-in-class drug comprising RNase1 fused to the Fc region of IgG1. It is designed to increase serum RNase activity to digest RNA associated immune complexes, thereby reducing Toll-like receptor (TLR) activation and subsequent production of type 1 interferon (IFN), B-cell proliferation, and autoantibody production – mechanisms that are key to pSS pathogenesis. IFN pathway dysregulation has also been implicated in fatigue. Objectives: To explore the clinical efficacy of RSLV-132 in improving patient-reported outcomes (PRO), particularly fatigue among patients with pSS. Methods: PSS patients with positive anti-Ro and IFN gene expression signature were randomised 3:1 to RSLV-132 10 mg/kg IV or placebo (PBO) at weeks 0, 1, 2, and then fortnightly until week 12. Use of hydroxycholoroquine, other immunomodulatory therapies or prednisolone > 10mg daily were not permitted. There was no minimum entry criteria for EULAR Sjogren's syndrome disease activity (ESSDAI) or EULAR Sjogren's syndrome patient reported index (ESSPRI). The primary endpoint was changes in gene or protein expression levels in blood indicative of reduced inflammation. Secondary endpoints, among others, included safety and tolerability, and changes in PRO between baseline and week 14 including ESSPRI, FACIT, Fatigue visual analogue score (0-100), Profile of fatigue (PRO-F (0-7)) and Neuropsychological tests. Results: Thirty patients were randomised (RSLV=22, PBO=8). Baseline clinical and demographic characteristics were comparable between groups. Two subjects randomised to active drug withdrew from the study before dosing. Among the patients receiving RSLV-132, the mental component of PRO-F improved by 1.53 points compared to worsening of 0.06 points in the PBO group (p=0.046). Consistently, there was a significant improvement in the RSLV-132 group in their Digital Symbol Substitution Test performance with a reduction of 16.4s in completing the test compared to an increase of 2.8s in the PBO group (p=0.024). The physical component of PRO-F improved by 0.8 points in the RSLV-132 group compared to improvement of 0.06 points in the PBO group (p=0.142). Similar trends were observed for ESSPRI and FACIT-F scores. There was no drug effect on ESSDAI but the baseline median ESSDAI scores were low for both groups (RSLV=3 (IQR (0, 11), PBO=5 (IQR (0, 18)). Treatment Emergent Adverse Events were reported by all participants and similar between arms; overall RSLV-132 was safe and well-tolerated. One SAE of parotitis in the RSLV-132 arm occurred 88 days after last dose of study drug and was considered unrelated to the RSLV-132. Analyses of the primary endpoints and other secondary endpoints are ongoing. Conclusion: RSLV-132 is a promising therapy to improve the symptoms of fatigue in patients with pSS, with a good safety profile. Further investigation of its use in pSS is warranted. Reference: [1] Study supported by Resolve Therapeutics Disclosure of Interests: Benjamin Fisher Consultant for: Novartis, Roche, MedImmune and BMS, Francesca Barone Grant/research support from: GlaxoSmithKline, Roche, UCB Pharma, Actelion, ONO Pharmaceutical, Consultant for: GlaxoSmithKline, Roche, Actelion, ONO Pharmaceutical, Kerry Jobling: None declared, Peter Gallagher: None declared, Victoria Macrae: None declared, Andrew Filby: None declared, Gillian Hulmes: None declared, Paul Milne: None declared, Emmanuella Traianos: None declared, Valentina Iannizzotto@bham.ac.uk : None declared, Alexandre Dumusc: None declared, Simon J. Bowman Grant/research support from: Previously UCB Pharma (to University of Birmingham) and Roche, Consultant for: 2016-7: Novartis, Mitsubishi Tanabe Pharma 2017-8: AstraZeneca, MedImmune, GFK, Xtlbio, ONO Pharmaceutical 2018-9: Novartis, AstraZeneca, UCB Pharma, Jessica Tarn: None declared, Dennis Lendrem: None declared, Daniel Burge Employee of: Resolve Therapeutics, Medical Monitor for the clinical trial, James Posada Shareholder of: Owns equity of Resolve Therapeutics, Employee of: Founder and CEO of Resolve Therapeutics, Wan-fai Ng Grant/research support from: I have research collaborations with Resolve Therapeutics, electroCore, GSK, and Abbvie., Consultant for: Novartis, GSK, Abbvie, MedImmune, Pfizer, BMS